IDENTIFICATION OF BASIC HEALTH INFORMATION AND KNOWLEDGE AT HIGH SCHOOLS IN SWAT RURAL AREAS (A WAY TOWARD VEBH MODEL IMPLEMENTATION) - Habib Ur Rahman (LPPM Universitas Terbuka, 2019)
Common diseases mostly occur due to lack of basic health information and knowledge to public at large. Therefore, basic health information and knowledge is very much important to reduce the outbreaks of different diseases especially in rural communities which is possible through proper education. Education is a natural and an inborn part of any community or society. High quality and healthy volunteers can be generated in a society by right education with full support of any kind of facility.The objective of this paper is to gather and identify information and knowledge about basic health from students and teachers. In this paper, first we study current basic health (information & knowledge) situation of teachers and students in high schools of District Swat (70% mountain rural areas and 30% urban areas), Khyber Pakhtunkhwa Pakistan. Secondly, find out the willingness of high school teachers and students for basic health information and knowledge using information communication technology (ICT) i.e. through a proposed “Virtual Education for Basic Health (VEBH)” model at high school level. For this purpose a pilot research survey was conducted in seven tehsils of district Swat which contained 119 high schools, including 77 male high schools and 42 female high schools.The respondents are willing to learn basic health information and knowledge through virtual and commented that it will be better for rural mountainous areas of Swat especially for female health. VEBH model will make the students aware about common diseases and ensure future healthy society.